Waste Retribution Revenue Management in Improving Community Environmental Cleanliness Services in Kelurahan Simpang Tanjung - Afrida Yani Siahaan; Nurhalizah Nurhalizah; Vinka Atira Werdy; Laiqah Syaziyah; Ayu Kurnia Sari (International Forum of Researchers and Lecturers, 2025)
In the densely populated Simpang Tanjung urban village, waste management is an important challenge in creating a clean and healthy environment. And for that, the effort made by the local government is to collect waste retribution as a source of local revenue (PAD) to be used to support cleaning operational costs. This study aims to improve cleaning services and evaluate community participation and to de-termine the effectiveness of waste retribution management. This research uses a descriptive qualitative approach by collecting data through direct interviews with cleaning officers, village officials and the community. This research shows that community participation in paying retribution is good and the collected funds are managed accountably. The management of waste retribution in Simpang Tanjung urban village runs quite well and effectively. However, there are several obstacles both internally and externally such as the lack of cleaning staff, limited waste transportation infrastructure and low public awareness about disposing of waste in the provided place. Therefore, it is important for the government to increase education about disposing of waste in its place and educate waste management in order to create a healthy and clean environment.